Survey of key management schemes for cluster networks - Jun LIU; Lin YUAN; Zhishang FENG (网络与信息安全学报)
With the rapid development of artificial intelligence and communication network technology, increasing attention has been paid to cluster intelligence.Cluster network is an important part of cluster intelligence, the security of information interaction has attracted much attention, and cluster key management has become a research hotspot in network information security.In recent years, many cluster key management schemes have been proposed, which provide effective solutions for information security interaction of complex cluster network systems.The existing cluster key management schemes were analyzed and summarized, and the future research direction and application scenarios were discussed.The typical three-layer cluster network model was introduced, including the control layer, cluster head layer and node layer.The characteristics of cluster network were summarized, such as large number and scale, dynamic topology change, and hierarchical cluster heterogeneity.According to the key management strategy and cluster networking scenarios, the cluster key management process before and after the network deployment was summarized.The key management evaluation index was analyzed from the aspects of security, efficiency, and flexibility.Then, three key management schemes including pre-distribution management, healing management and dynamic management were discussed.Their basic ideas, advantages and disadvantages were analyzed, and their performance from the aspects of techniques, security, flexibility, and efficiency was compared.Besides, the research hotspots related to cluster key management were prospected from cross-domain heterogeneity, cluster authentication, healing mechanism, and technology fusion.The security function of cluster key management in future application scenarios such as ubiquitous IoT, all-domain operation, and smart city was discussed.